COMPARATIVE ASSESSMENT OF VARIETIES OF THE SPRING TRITICALE - Mefodyev Georgiy Anatolyevich; Shashkarov Leonid Gennadievich; Semenov Vladimir Grigoryevich; Baimukanov Dastanbek Asylbekovich; Karibayeva Dilaram Keudenbayevna (Scientific Journal of Pedagogy and Economics, 2019)
The relevance of the studies is justified by the fact that in the Chuvash Republic, the triticale was grown on an area of 2.6 thousand hectares, mainly winter varieties. In recent years, research has focused on selection work with spring triticale. The determination and study of the new basic material are always relevant because the quality of the basic material always determines the efficiency of the selection work. The aim of the work was to carry out a comparative assessment of new varieties of spring triticale in the conditions of the Chuvash Republic. An assessment of new varieties of spring triticale in the conditions of the Chuvash Republic was carried out. It is revealed that the Saur variety is characterized by the largest number of productive stems, weight of kernels from spike and thousand-kernel weight. The number of productive stems was the lowest in the Rovnya variety. This variety showed the minimum values and the number of spikelets in the ear. At the same time, in the Rovnya variety, the number of kernels in the spike was the largest. The Ulyana variety was inferior to all other varieties by the kernel weight from 1 spike and by thousand-kernel weight. The variety of Khaikar significantly exceeded the standard for the number of productive stems, kernel weight from 1 spike and the 1000-kernel mass, and the number of spikelets and kernels in the spike was at the level of Ulyana. The Saur and Khaikar varieties significantly outperform the standard. Field germination of seeds was rather low. In the Ulyana variety, the seeding rate did not have a significant effect on this indicator. It ranged from 56.0 to 56.5%. The density of shoots depended on both the seeding rate and the variety. The number of plantlings with an increase in the seeding rate increased in the Ulyana variety from 225 to 339 and in the Khaikar variety – 276 to 372 pieces/m2 . However, with the increase in the seeding rate, the survival ability and preservation of plants decreased. A particularly sharp decrease was characteristic of the seeding rate of 6 million germinated seeds. The optimal seeding rate of varieties of spring triticale in the conditions of the Chuvash Republic is 5 million germinated seeds per 1 hectare.